Penggunaan Ampas Sagu Ampas Tahu Fermentasi dengan Monascus purpureus dalam Ransum Terhadap Performa Puyuh Petelur - S.A. Latif; Nuraini Nuraini; Mirzah Mirzah; A. Djulardi (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
The aim of this research is to know the effect of utilization of combination sago rotb waste and tofu waste fermented by Monascus purpureus in egg quail (Coturnix-coturnix japonica) ration on their egg performance. About 200 quails were used in completely randomized design with 4 treatments (0.5%; 10% and 15%) of different level of combination sago rotb waste and tofu waste fermented in ration, and each treatment are replicated for 5 times. Ration are arranged iso protein (20%) and iso calory (2,800 kcal/kg). The parameters are: egg production, egg weigth and body weight. The result showed that the utilization of combination of sago rotb and tofu waste fermented by Monascus purpureus was not affected egg quail performance significantly (P>0.05). Inconclusion, the utilization of combination sago rotb waste and tofu waste fermented by Monascus purpureus until 15% in quail ration increased egg production with quail day scoring 80%, egg weight is 9.70 g/egg, and body weight is 56.12 g/quail.